PAJAK DAN ZAKAT DILIHAT DARI HUKUM ISLAM - Mohammad Solekhan (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
State-acceptance is very required to improve the people prosperity. There is an acceptance might be done in Islam either by tithe or tax. However, in theimplementation of taxation, Islam Law has given clear guidance through it collection either by Moslem or Non-Moslem. There is an obligation for Moslem to pay for tax if a pay office is requiring it. The obligation as observance toward ulil amri, as called within the holy book of An-Nisa verse 59, is that means: “The faithful be obedient to Allah and it prophets and ulil amri between you are. Then if you different in opinion about something else, so please bring it back to Allah (Al Quran) and Prophet (Sunah), if you really faith to Allah and afterwards. That is more prominent (to you) and gives better result.